Metformin is cytotoxic against cervical cancer Helavia modulation (p53, caspase-3, bcl2, cox-1,Cyclin-d1) genes expression - MOHAMED A. S. AL-GHUSSEIN; ABBAS MOHAMED (International Journal of Pharma and Bio Sciences, 2017)
Cervical cancer is the second female cancer worldwide. Could it be treated safely and efficiently? Would these women not losing their fertility for treatment? We aimed to estimate whether metformin treatment against cervical cancer HeLa cell line could affect cells viabilityor not and to evaluate the genes expression of p53, caspase-3, Bcl2, COX-1 and cyclin-D1 as an apoptotic and proliferation markers genes.HeLa cell line was cultured and treated with different concentrations of metformin. Cells viability was investigated by MTT proliferation assay. Cells was treated by metformin for 48 h and 72 h and harvested for RNA extraction. RNA was transformed to cDNA and p53, caspase-3, Bcl2, COX-1 and cyclin-D1 genes’ expression were assessed by qPCR.Metformin was cytotoxic by 66% death at1000 µg/mLfor HeLa cervix cancer cells and reduced the survival fraction in a dose response relationship. Metformin affects many genes’ expression that reflects life and death. P53 and caspase-3 genes’ expression were raised by the drug effect while Bcl-2, COX-1 and cyclin-D1 genes’ expression levels were reduced.Metformin showed potent apoptotic activities against cervical cancerHeLa cell line through the elevation of p53 and caspase-3 and the elevation of Bcl-2, COX-1 and cyclin-D1 genes’ expression. Metformin could be the new, safe and effective treatment against cervical cancer.